Effects of Personality Types on the Performance of Educational Teams - Juan Manuel Criado; Gema Gutiérrez; Emilio L. Cano; Javier Garzás; María Teresa González de Lena; Javier M. Moguerza; Juan José Fernández Muñoz (Behavioral Sciences)
The objective of this study is to explore how various personality types correlate with enhanced work performance. The Enneagram type of the participants in the experiment was established by using the simplest version of the Riso–Hudson test. A two-way ANOVA was performed under the principles of the Design of Experiments, which allowed the identification of main effects and interactions in the response, i.e., the marks of the university teams. We found that the interactions between certain Enneagram types seem to increase the average performance marks as a primary effect. Conversely, when certain Enneagram types coincided within a team, the marks significantly decreased, posing a risk to project success. According to our results, the Enneagram framework may be used as a preliminary stage for identifying potential team members for future projects.